Properties of Spent Active Coke Particles Analysed via Comminution in Spouted Bed - Bronislaw Buczek (The Scientific World Journal)
Samples of active coke, fresh and spent after cleaning flue gases from communal waste incinerators, were investigated. The outer layers of both coke particles were separately removed by comminution in a spouted bed. The samples of both active cokes were analysed by means of densities, mercury porosimetry, and adsorption technique. Remaining cores were examined to determine the degree of consumption of coke by the sorption of hazardous emissions (SO2, HCl, and heavy metals) through its bed. Differences in contamination levels within the porous structure of the particles were estimated. The study demonstrated the effectiveness of commercial active coke in the cleaning of flue gases.